2022
DOI: 10.4103/jomfp.jomfp_284_21
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous jaw lesions

Abstract: Context: Jaw bones can be afflicted by to a diverse group of lesions ranging from developmental, reactive/inflammatory, cystic lesions to tumors and tumor-like lesions Objectives: The objective of this study is to determine the relative frequency, demographic and pathologic profiles of patients with intraosseous jaw lesions from Thailand. Subjects and Methods: Biopsy records from 1995 to 2019 were reviewed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In overall, male patients with CsOJ outnumbered their female counterpart as in previous studies (Aquilanti et al, 2021; Butt et al, 2011; Del Corso et al, 2014; Grossmann et al, 2007; Jaeger et al, 2017; Johnson et al, 2013; Jones et al, 2006; Kambalimath et al, 2014; Kammer et al, 2020; Lo Muzio et al, 2017; Mosqueda‐Taylor et al, 2002; Ochsenius et al, 2007; Tamiolakis et al, 2019; Tekkesin et al, 2012; Tortorici et al, 2008), especially studies from Southeast Asia and the Middle East and North America (Dhanuthai et al, 2022; Sharifian & Khalili, 2011; Zhang et al, 2010) except in the study by de Souza et al (2010) in which the reverse was true. Moreover, OCs, NOCs as well as Cysts not otherwise specified all consistently demonstrated a male predilection.…”
Section: Discussionmentioning
confidence: 99%
“…In overall, male patients with CsOJ outnumbered their female counterpart as in previous studies (Aquilanti et al, 2021; Butt et al, 2011; Del Corso et al, 2014; Grossmann et al, 2007; Jaeger et al, 2017; Johnson et al, 2013; Jones et al, 2006; Kambalimath et al, 2014; Kammer et al, 2020; Lo Muzio et al, 2017; Mosqueda‐Taylor et al, 2002; Ochsenius et al, 2007; Tamiolakis et al, 2019; Tekkesin et al, 2012; Tortorici et al, 2008), especially studies from Southeast Asia and the Middle East and North America (Dhanuthai et al, 2022; Sharifian & Khalili, 2011; Zhang et al, 2010) except in the study by de Souza et al (2010) in which the reverse was true. Moreover, OCs, NOCs as well as Cysts not otherwise specified all consistently demonstrated a male predilection.…”
Section: Discussionmentioning
confidence: 99%
“…4 Most cases of odontogenic tumors are diagnosed in young adults, with a median age of 10 to 38 years, with no significant sex predilection. [5][6][7][8] In Asia and North America, the mean (AE standard deviation) age of patients with ameloblastoma is 38.27 AE 17.78 years. 6 More specifically, in the Thai population, Kitisubkanchana et al reported an average age of 34.9 years; 7 Soylu et al reported an average age of 39.35 years in Turkey (Middle Anatolia); 8 and older sources report a mean of 36 years.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] In Asia and North America, the mean (AE standard deviation) age of patients with ameloblastoma is 38.27 AE 17.78 years. 6 More specifically, in the Thai population, Kitisubkanchana et al reported an average age of 34.9 years; 7 Soylu et al reported an average age of 39.35 years in Turkey (Middle Anatolia); 8 and older sources report a mean of 36 years. 5 Approximately 80% of ameloblastomas occur in the mandible, usually in the posterior region, and represent only 1% of all oral/head and neck tumors.…”
Section: Discussionmentioning
confidence: 99%